Kajian Komparatif terhadap Perbedaan Dinamika Batas Usia dan Perizinan Perkawinan antara Indonesia dan Malaysia - Harish Faqihuddin Assahmi; Raka Rahman Pangestu; Rayhan Rizwaantya (HOKI : Journal of Islamic Family Law, 2026)
This study examines the comparative development of minimum marriage age regulations in Indonesia and Malaysia, with particular attention to the underlying reasons for legal reform and the mechanisms for granting permission for underage marriage. The research employs a normative legal research method using statutory and comparative law approaches. The data consist of secondary sources, including legislation, court decisions, academic books, journals, and other relevant legal materials. The findings reveal that Indonesia raised the minimum marriage age for both men and women to 19 years through Law Number 16 of 2019, following Constitutional Court Decision Number 22/PUU-XV/2017, which declared the previous age disparity discriminatory and contrary to the constitutional rights of children. In contrast, Malaysia’s initiative to raise the minimum marriage age for women was primarily driven by political commitments and pressure from women’s rights organizations and UNICEF, as reflected in the Pakatan Harapan coalition’s manifesto. Nevertheless, the implementation has been uneven due to the decentralized authority of Islamic family law at the state level. This study concludes that differences in legal structure, political dynamics, and institutional authority account for the varying pace and scope of minimum marriage age reforms in Indonesia and Malaysia.